High-rigidity flame-retardant polypropylene plastic and preparation method thereof

By adding long glass fibers and phosphorus-nitrogen intumescent halogen-free flame retardants to polypropylene materials, combined with lubricants and antioxidants, the problems of poor rigidity and insufficient flame retardancy of polypropylene materials are solved, achieving high rigidity and Highly flame-retardant polypropylene material ensures product dimensional stability and safety.

CN119331343APending Publication Date: 2025-01-21QINGDAO GON TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411355163.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In actual applications, polypropylene materials have poor rigidity, large shrinkage, unstable product size, and do not have flame retardant and fire-proof requirements, which are extremely flammable and have great harm.

Method used

Use average polyocylylene and common polyetryth as the main material, and add long glass fiber and phosphorus-nitrogen-nitrogen-inflated flame-free flame retardant, combined with lubricants and antioxidants, and retain the long needle-shaped structure of glass fiber through side feeding processing process , Improve the rigidity and flame retardability of the material.

Benefits of technology

It significantly improves the rigidity and flame retardant performance of polypropylene materials, reduces the contraction rate, ensures the stability of the product size, and achieves a low flame retardant effect of low smoke and non -toxic flame retardant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005063404890000091
    Figure BDA0005063404890000091
  • Figure BDA0005063404890000101
    Figure BDA0005063404890000101
  • Figure BDA0005063404890000141
    Figure BDA0005063404890000141
Patent Text Reader

Abstract

The invention relates to the field of high polymer materials, and particularly discloses a high-rigidity flame-retardant polypropylene plastic and a preparation method thereof. The high-rigidity flame-retardant polypropylene plastic is prepared from the following raw materials in percentage by weight: 20 to 30 percent of homo-polypropylene, 20 to 30 percent of co-polypropylene, 15 to 20 percent of long glass fiber, 20 to 30 percent of halogen-free flame retardant, 2 to 8 percent of flexibilizer, 0.5 to 1.5 percent of antioxidant and 0.5 to 1.5 percent of lubricant, the main components of the flame retardant are compounded of piperazine pyrophosphate and melamine polyphosphate. The polypropylene material provided by the invention has the advantages of high tensile and bending strength, small after-shrinkage rate, strong dimensional stability, efficient flame retardance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and more specifically, to a high-rigidity flame-retardant polypropylene plastic and a preparation method thereof. Background Art

[0002] Plastic is a polymer material with special properties. It is light, chemically stable, corrosion-resistant, insulating, easy to shape, and low-cost. It is widely used in the electronics industry, automobile manufacturing, aerospace, and industrial fields. Polypropylene is a semi-crystalline thermoplastic formed by catalytic polymerization of propylene monomers. Polypropylene has the characteristics of low price, low density, yellowing resistance, aging resistance, corrosion resistance, and good molding and processing, which makes the application of polypropylene in the fields of automobiles, home appliances, and medical treatment increase year by year.

[0003] In recent years, the rapid development of the electronics, construction, aviation and automobile industries has put forward higher requirements for the performance of plastics. Among them, flame-retardant plastics are not easy to burn, have a low flame propagation rate, a low mass loss rate and heat release rate, and have a certain degree of self-extinguishing properties. However, polypropylene materials have poor flame retardancy and cannot meet flame retardant requirements. Halogen flame retardants are often used, and the combustion process will release hydrogen halides that cause serious harm to the human body. In addition, polypropylene has a large shrinkage rate, and thick-walled products are prone to dents, making it difficult to meet the requirements for some parts with high dimensional accuracy.

[0004] With respect to the above-mentioned related technologies, the inventors found that polypropylene materials have poor rigidity, large shrinkage, and unstable product dimensions in practical applications; they do not meet the flame retardant and fireproof requirements, are extremely easy to burn, and are extremely harmful. Summary of the invention

[0005] In order to make polypropylene not only have a certain impact strength, but also improve rigidity and flame retardancy, the present application provides a high-rigidity flame-retardant polypropylene plastic and a preparation method thereof.

[0006] In the first aspect, the present application provides a high-rigidity flame-retardant polypropylene plastic, which adopts the following technical solution:

[0007] A high-rigidity flame-retardant polypropylene plastic comprises the following raw materials in weight percentage: 20-30% homopolymer polypropylene, 20-30% copolymer polypropylene, 15-20% long glass fiber, 20-30% halogen-free flame retardant, 2-8% toughening agent, 0.5-1.5% antioxidant and 0.5-1.5% lubricant, wherein the halogen-free flame retardant is a phosphorus-nitrogen expansion type halogen-free flame retardant. The length of the long glass fiber is 100-150 mm and the diameter is 5-15 μm.

[0008] By adopting the above technical scheme, homopolymer polypropylene and copolymer polypropylene are used as the main materials, and a certain amount of long glass fibers are added, which have a certain fibrous and needle-like structure and are dispersed in the polypropylene material, so that the mechanical properties of the matrix can be significantly improved, and the rigidity and dimensional stability of the product can be improved. The phosphorus-nitrogen expandable halogen-free flame retardant has the advantages of high flame retardant carbonization efficiency, low smoke and non-toxicity. The lubricant has the functions of internal and external dispersion and lubrication, so that the flame retardant and filler in the material formula are fully dispersed, the friction coefficient of the extruded surface of the polypropylene material is reduced, and the surface of the product is smooth, flat and uniform. The antioxidant can prevent the polypropylene from decomposing during high-temperature extrusion, thereby obtaining a polypropylene material that not only has a certain mechanical strength, but also has a greatly reduced shrinkage rate and has very high rigidity and flame retardancy.

[0009] Optionally, the polypropylene plastic comprises the following raw materials in percentage by weight: 25% homopolypropylene, 25% copolymer polypropylene, 15% long glass fiber, 29% halogen-free flame retardant, 5% toughening agent, 0.5% antioxidant, and 0.5% lubricant.

[0010] By adopting the above technical solution, the dosage of each raw material is more accurate, so that the manufactured polypropylene material has high rigidity, good flame retardant performance, small shrinkage and good dimensional stability.

[0011] Optionally, the phosphorus-nitrogen intumescent halogen-free flame retardant comprises high-polymerization II type melamine polyphosphate salt, piperazine pyrophosphate and polytetrafluoroethylene in a mass ratio of 5:1-1.2:0.05-0.1.

[0012] By adopting the above technical scheme, the high-polymerization II type melamine polyphosphate salt has high phosphorus content, high nitrogen content, large molecular weight and precipitation resistance, and has the advantages of low price, low toxicity, safe use, etc., high flame retardant efficiency, less smoke, non-toxic, no harmful gas and molten droplets when heated and burned, and it generates a dense carbon layer to play a heat insulation and oxygen isolation role to achieve the purpose of flame retardancy. Piperazine pyrophosphate is used to flame retardant the high-polymerization II type melamine polyphosphate salt. During the combustion process, piperazine pyrophosphate and melamine polyphosphate salt undergo a series of esterification reactions such as carbonization, and at the same time, the polyphosphate trimer Phosphoric acid and polyphosphoric acid produced by the decomposition of cyanamide salt can promote the carbonization of polypropylene and form an expanded carbon layer on the surface of the polypropylene material, which hinders the diffusion of combustible gases produced by cracking to the flame surface and the diffusion of external heat and oxygen to the inside of the material, playing a role of physical heat insulation and oxygen isolation, and well protecting the further degradation and combustion of the internal material, thereby improving the flame retardancy of the material; hot molten droplets are easily generated during the heating process of the material. Adding a small amount of polytetrafluoroethylene can form a net-like structure to wrap the hot molten droplets when the material is heated, avoiding the risk of secondary fire caused by the hot molten droplets, and further improving the flame retardancy of polypropylene.

[0013] Optionally, the lubricant includes a stearic acid lubricant and a silicone masterbatch in a mass ratio of 1:0.8-1.2.

[0014] By adopting the above technical solution, the compatibility of stearic acid lubricants, silicone masterbatches and polypropylene matrix is ​​good, which can improve the dispersibility of flame retardants and long glass fibers, improve the processing efficiency during extrusion of the blended material, overcome material bonding, improve the smoothness and glossiness of the finished product, and improve the appearance of the finished product. As an excellent external lubricant, silicone masterbatch can improve the dispersion of materials and reduce extrusion die scale, reduce equipment wear, increase discharge speed, and improve the dispersibility of long glass fibers and flame retardants. Stearic acid lubricants and silicone masterbatches cooperate with each other through their own internal and external lubrication, and can also fully disperse the flame retardants and long glass fibers in the material formula, reduce the friction coefficient of the extruded surface, and make the surface of the polypropylene material smoother and flatter.

[0015] Optionally, the silicone masterbatch is prepared by the following method: dispersing silicone powder in anhydrous ethanol to prepare a dispersion with a concentration of 8-10wt%; adding attapulgite to deionized water to prepare a suspension with a concentration of 3-5wt%; adding silica sol to deionized water to prepare a silica sol solution with a concentration of 3-5wt%;

[0016] The dispersion, suspension and silica sol solution are mixed and spray-dried to obtain silicone masterbatch, wherein the mass ratio of silicone powder, silica sol and attapulgite is 2-2.5:2.5-3:5.

[0017] By adopting the above technical scheme, a large number of hydroxyl groups and fibrous crystal structures on the surface of attapulgite make it have strong adsorption properties. Attapulgite and silicon dioxide can be completely and tightly adsorbed together in water. By adding silicone powder to the suspended aqueous solution of attapulgite and silicon dioxide, the silicone powder can be loaded in the attapulgite and silicon dioxide. The various components are isolated from each other to form a loose structure. When added to polypropylene, the loose structure is easy to disperse in the mass under the shearing action of the external screw. The addition of attapulgite and silicon dioxide can improve the rigidity of polypropylene. Spray drying avoids the agglomeration of attapulgite, silicon dioxide and silicone powder, and the dispersibility is improved. Attapulgite and silicon dioxide become nucleating agents, and the amorphous part of the polypropylene material that originally could not crystallize is transformed into crystals, thereby obtaining A higher crystallinity can reduce the spherulite size of polypropylene, improve the bonding strength of the spherulite interface, make the crystals denser, reduce the scattering and refraction of incident light, and increase the glossiness. Moreover, after the spherulites change from a small number of large-sized crystals to a large number of small-sized dense crystals, the refinement of the spherulites can make the material absorb more energy and improve the impact strength. The silicone powder has a low friction coefficient between molecular chains and is evenly dispersed and embedded in the polypropylene molecular chain and evenly distributed in the polypropylene structure, which reduces the friction between the polypropylene molecular chain segments and the friction between the polypropylene molecular chain segments and the processing equipment, improves the sliding properties of polypropylene, enhances the lubrication effect, improves the extrusion performance, improves the lubricity of the polypropylene material, makes the surface of the polypropylene material smoother and flatter, and significantly improves the glossiness.

[0018] Optionally, the melt index of the homopolypropylene is 10-20 g / 10 min, and the melt index of the copolymer polypropylene is 20-30 g / 10 min.

[0019] By adopting the above technical scheme, copolymer polypropylene and homopolypropylene with strong formability and good fluidity are used as base materials, and a uniformly blended polypropylene product can be produced at a lower extrusion temperature, and the homopolypropylene and copolymer polypropylene blended with the above melt index have strong tensile properties and high bending modulus.

[0020] Optionally, the toughening agent is ethylene-octene copolymer, and the melt index at 190° C. and 2.16 kg is 20 g / 10 min.

[0021] By adopting the above technical solution, the ethylene-octene copolymer can better improve the compatibility of components such as copolymer polypropylene, homopolypropylene, and long glass fibers, and improve the mechanical strength, especially the toughness, of the polypropylene material.

[0022] Optionally, the antioxidant is selected from one or more of phosphite antioxidants, thioester antioxidants and hindered antioxidants.

[0023] By adopting the above technical solution, the antioxidant can protect the polypropylene to prevent the polypropylene from being degraded during extrusion due to the high processing and shearing temperature and the long residence time of the polypropylene in the extruder, thereby reducing the mechanical strength.

[0024] In a second aspect, the present application provides a method for preparing a high-rigidity flame-retardant polypropylene plastic, using the following technical solution:

[0025] A method for preparing high-rigidity flame-retardant polypropylene plastic comprises the following steps:

[0026] Preparation of halogen-free flame retardant: high polymerization degree II type polyphosphate melamine salt is stirred at high speed at 30-40°C for 10-12 minutes, piperazine pyrophosphate carbonizing agent is added, the temperature is raised to 60-70°C, stirred at high speed for 60-70 minutes, cooled to 20-30°C, polytetrafluoroethylene is added while stirring, stirred at low speed for 5-8 minutes, cooled for 20-25 minutes, and the halogen-free flame retardant is obtained;

[0027] Raw material selection: according to the mass percentage, weigh 20-30% homopolypropylene, 20-30% copolymer polypropylene, 15-20% long glass fiber, 20-30% halogen-free flame retardant, 2-8% toughening agent, 0.5-1.5% antioxidant and 0.5-1.5% lubricant respectively;

[0028] Mixing and stirring: adding the halogen-free flame retardant to the long glass fiber, stirring at 20-30°C for 30-40 minutes, to obtain a No. 1 material package; mixing the homopolymer polypropylene, copolymer polypropylene, toughening agent, antioxidant and lubricant, stirring at 20-30°C for 30-40 minutes, to obtain a No. 2 material package;

[0029] Blending modification: Add No. 2 material package to the main feeding port, add No. 1 material package through the side feeding port, the extrusion temperature is 180-220℃, extrude the strip material, and cool;

[0030] Air-cooling pressing: Arrange the strip materials in sequence at a spacing of 2-5 cm, cool them with cold air at 15-16°C for 25-35 minutes, press them at a pressure of 1-2 MPa for 5-10 seconds, and package them to obtain high-rigidity flame-retardant polypropylene materials.

[0031] By adopting the above technical scheme, high polymerization degree II polyphosphate melamine salt, piperazine pyrophosphate and polytetrafluoroethylene are compounded to form a flame retardant that is halogen-free, low-smoke, non-corrosive and non-toxic gas-generating; and the long glass fiber and halogen-free flame retardant are fed through the side feeding process to reduce the influence of the screw extrusion length and time, which can not only ensure the flame retardancy, but also retain the long needle structure of the glass fiber, improve the rigidity and reduce the shrinkage rate. This method has the advantages of rigorous logic, green environmental protection, wide material sources, easy processing, low energy consumption and low cost, and it is endowed with two major functions of high rigidity and high flame retardancy, and has outstanding advantages in performance and safety.

[0032] Optionally, during extrusion, the screw speed is 320-350r / min and the extrusion power is 260-280W.

[0033] By adopting the above technical solution, too high a rotation speed during extrusion can easily cause thermal degradation of the flame retardant, while too low a rotation speed can cause poor dispersion and plasticization.

[0034] In summary, this application has the following beneficial effects:

[0035] 1. Since the present application uses homopolymer polypropylene and copolymer polypropylene as the base material, and adds long glass fiber, phosphorus-nitrogen intumescent halogen-free flame retardant, lubricant and antioxidant, etc. Among them, the needle-like structure of the long glass fiber under the side-feed processing technology can significantly improve the rigidity of polypropylene and reduce the shrinkage rate, giving the product good mechanical strength and dimensional stability.

[0036] 2. In this application, high polymerization degree II melamine polyphosphate salt, piperazine pyrophosphate and polytetrafluoroethylene are preferably used to prepare halogen-free flame retardants. The above compounding method is green, environmentally friendly, low-smoke and non-toxic; the flame retardant esterifies to carbon at a fast reaction rate, and the dense carbon layer formed isolates oxygen and heat, which can make the product easily achieve UL94 V0 flame retardant grade.

[0037] 3. In the present application, stearic acid lubricants and silicone masterbatches are preferably used as lubricants, and the silicone masterbatch is made of attapulgite, silica and silicone powder. The silicone powder is loaded on attapulgite and silica to form a loose structure isolated from each other. When polypropylene is extruded, the loose structure is easy to disperse through the shearing action of the screw, thereby improving the crystallinity and refining the spherulites, reducing the scattering and refraction of the incident light, and improving the gloss of the product. DETAILED DESCRIPTION

[0038] Preparation Examples 1-4 of Silicone Masterbatch

[0039] Preparation Example 1: Disperse silicone powder in anhydrous ethanol to prepare a dispersion with a concentration of 10wt%; add attapulgite to deionized water to prepare a suspension with a concentration of 5wt%; add silica sol to deionized water to prepare a silica sol solution with a concentration of 5wt%, the silicone powder is selected from Dongwanshanyi Plastics, model SY-306A, the silica sol is selected from Gelling Hongxinda Biotechnology, model HXD-02, and the attapulgite is selected from Anhui Mingmei Minerals, model 701A;

[0040] The dispersion, suspension and silica sol solution were mixed and spray-dried to obtain silicone masterbatch. The mass ratio of silicone powder, silica sol and attapulgite was 2.5:2.5:5. The spray drying inlet temperature was 150°C and the outlet temperature was 60°C.

[0041] Preparation Example 2: Disperse silicone powder in anhydrous ethanol to prepare a dispersion with a concentration of 8wt%; add attapulgite to deionized water to prepare a suspension with a concentration of 3wt%; add silica sol to deionized water to prepare a silica sol solution with a concentration of 3wt%, the silicone powder is selected from Dongwanshanyi Plastics, model SY-306A, the silica sol is selected from Gelling Hongxinda Biotechnology, model HXD-02, and the attapulgite is selected from Anhui Mingmei Minerals, model 701A;

[0042] The dispersion, suspension and silica sol solution were mixed and spray-dried to obtain silicone masterbatch. The mass ratio of silicone powder, silica sol and attapulgite was 2:3:5. The spray drying air inlet temperature was 150°C and the air outlet temperature was 60°C.

[0043] Preparation Example 3: The difference from Preparation Example 1 is that attapulgite is not added.

[0044] Preparation Example 4: The difference from Preparation Example 1 is that no silica sol is added.

[0045] Example

[0046] Example 1: A high rigidity flame retardant polypropylene plastic, the raw material dosage is shown in Table 1, wherein the melting index of homopolymer polypropylene is 15g / 10min, the model is Formosa Plastics Ningbo 1120, the melting index of copolymer polypropylene is 25g / 10min, the model is South Korea SK B380G, the length of the long glass fiber is 120mm, the diameter is 10μm, the antioxidant is phosphite antioxidant 168, the lubricant is calcium stearate, the toughening agent is ethylene-octene copolymer, the melt index at 190℃ / 2.16kg is 20g / 10min, the model is Dow 8402, the halogen-free flame retardant is a phosphorus-nitrogen expandable halogen-free flame retardant, including high-polymerization II type melamine polyphosphate salt, piperazine pyrophosphate and polytetrafluoroethylene in a mass ratio of 5:1:0.1, the high-polymerization II type melamine polyphosphate salt is selected from Shifang Changfeng Chemical, model CF-MPP31, and the piperazine pyrophosphate is selected from Qingyuan Putifufo Chemical Co., Ltd.

[0047] The method for preparing the above-mentioned high-rigidity flame-retardant polypropylene material comprises the following steps:

[0048] S1. Preparation of halogen-free flame retardant: high polymerization degree II type polyphosphate melamine salt was stirred at high speed at 30°C for 10 minutes, piperazine pyrophosphate carbonizing agent was added, the temperature was raised to 60°C, stirred at high speed for 65 minutes, cooled to 20°C, polytetrafluoroethylene was added while stirring, stirred at low speed for 6 minutes, cooled for 25 minutes, and halogen-free flame retardant was obtained;

[0049] S2. Raw material selection: weigh each raw material according to the raw material amount in Table 1;

[0050] S3, mixing and stirring: adding the halogen-free flame retardant to the long glass fiber, stirring at 30°C for 40 minutes, to prepare a No. 1 material package; mixing the homopolymer polypropylene, copolymer polypropylene, toughening agent, antioxidant and lubricant, stirring at 30°C for 40 minutes, to prepare a No. 2 material package;

[0051] S4, blending modification: add No. 2 material package to the main feeding port of the twin-screw extruder, add No. 1 material package to the twin-screw extruder through the side feeding port, the extrusion temperature is 200°C, extrude the strip material, cool it, the screw speed is 340r / min, and the extrusion power is 270W;

[0052] S5. Air-cooling pressing: Arrange the strip materials in sequence and place them in an air cooler with a spacing of 2 cm. Turn on the air cooler and set the temperature to 15°C. Continue air cooling for 30 minutes. Turn off the air cooler, take out the strip materials, place them in a rolling and forging machine, press them at a pressure of 1 MPa for 6 seconds, bundle and package them to obtain high-rigidity flame-retardant polypropylene materials.

[0053] Table 1 Amount of raw materials used for high rigidity flame retardant polypropylene materials in Examples 1-4

[0054]

[0055]

[0056] Embodiment 2: A high rigidity flame retardant polypropylene material, the raw material dosage is as shown in Table 1, wherein the melting index of homopolymer polypropylene is 10g / 10min, the model is Yanshan Petrochemical K1008, the melting index of copolymer polypropylene is 27g / 10min, the model is Yangzi Petrochemical K9927, the length of long glass fiber is 120mm, the diameter is 10μm, the antioxidant is phosphite antioxidant 168, the lubricant is sodium stearate, the toughening agent is ethylene-octene copolymer, the melting index under 190℃ / 2.16kg conditions is 20g / 10min, the model is Dow 8402, and the halogen-free flame retardant is a phosphorus-nitrogen expansion type halogen-free flame retardant, including high polymerization degree II type polyphosphate melamine salt, piperazine pyrophosphate and polytetrafluoroethylene in a mass ratio of 5:1.2:0.05.

[0057] The method for preparing the above-mentioned high-rigidity flame-retardant polypropylene material comprises the following steps:

[0058] S1. Preparation of halogen-free flame retardant: adding high polymerization degree II type polyphosphate melamine salt into a high-speed mixer, stirring at 200 r / min for 20 min at 25°C, the volume of polyphosphate melamine salt being one third of the capacity of the high-speed mixer, then adding piperazine pyrophosphate, heating to 60°C, stirring at 500 r / min for 40 min, cooling to 20°C, adding polytetrafluoroethylene while stirring, stirring for 5 min, cooling for 20 min, and obtaining halogen-free flame retardant;

[0059] S2. Raw material selection: weigh each raw material according to the raw material amount in Table 1;

[0060] S3, mixing and stirring: adding the halogen-free flame retardant to the long glass fiber, stirring at a speed of 200 r / min for 25 minutes at 25°C to obtain a material package No. 1; mixing the homopolymer polypropylene, copolymer polypropylene, toughening agent, antioxidant and lubricant, stirring at a speed of 500 r / min for 40 minutes at 25°C to obtain a material package No. 2;

[0061] S4, blending modification: add No. 2 material package to the main feeding port of the twin-screw extruder, add No. 1 material package to the twin-screw extruder through the side feeding port, extrusion temperature is 195 ° C, extrusion strip material, cooling, screw speed is 340r / min, extrusion power is 275W;

[0062] S5. Air-cooling pressing: Arrange the strip materials in sequence and place them in an air cooler with a spacing of 4 cm. Turn on the air cooler and set the temperature to 15°C. Continue air cooling for 30 minutes. Turn off the air cooler, take out the strip materials, place them in a rolling and forging machine, press them at a pressure of 2 MPa for 5 seconds, bundle and package them to obtain high-rigidity flame-retardant polypropylene materials.

[0063] Example 3-4: A high-rigidity flame-retardant polypropylene material, which is different from Example 1 in that the amounts of raw materials used are as shown in Table 1.

[0064] Example 5: A high-rigidity flame-retardant polypropylene material, which is different from Example 1 in that the melt index of homopolypropylene is 6 g / 10 min and is selected from Shanghai Petrochemical Y600.

[0065] Example 6: A high-rigidity flame-retardant polypropylene material, which is different from Example 1 in that the melt index of the homopolymer polypropylene is 20 g / 10 min and is selected from Indian Petrochemical H200MA.

[0066] Example 7: A high-rigidity flame-retardant polypropylene material, which is different from Example 1 in that the melt index of the copolymerized polypropylene is 30 g / 10 min, and is selected from Beijing Yanshan K9035.

[0067] Example 8: A high-rigidity flame-retardant polypropylene material, which is different from Example 1 in that the melt index of the copolymerized polypropylene is 10 g / 10 min and is selected from Korean Hyosung J640.

[0068] Example 9: A high-rigidity flame-retardant polypropylene material. The difference from Example 1 is that the lubricant includes calcium stearate and silicone masterbatch in a mass ratio of 1:1.2, and the silicone masterbatch is made by Preparation Example 1.

[0069] Example 10: A high-rigidity flame-retardant polypropylene material. The difference from Example 1 is that the lubricant includes calcium stearate and silicone masterbatch in a mass ratio of 1:0.8, and the silicone masterbatch is made by Preparation Example 2.

[0070] Example 11: A high-rigidity flame-retardant polypropylene material. The difference from Example 1 is that the lubricant includes calcium stearate and silicone masterbatch in a mass ratio of 1:1.2, and the silicone masterbatch is made by Preparation Example 3.

[0071] Example 12: A high-rigidity flame-retardant polypropylene material. The difference from Example 1 is that the lubricant includes calcium stearate and silicone masterbatch in a mass ratio of 1:1.2, and the silicone masterbatch is made by Preparation Example 4.

[0072] Example 13: A high-rigidity flame-retardant polypropylene material. The difference from Example 1 is that the lubricant includes calcium stearate and silicone masterbatch in a mass ratio of 1:1.2, and the silicone masterbatch model is KJ-A01.

[0073] Example 14: A high-rigidity flame-retardant polypropylene material, which differs from Example 1 in that no piperazine pyrophosphate carbonizing agent is added to the phosphorus-nitrogen expandable halogen-free flame retardant.

[0074] Example 15: A high-rigidity flame-retardant polypropylene material, which differs from Example 1 in that polytetrafluoroethylene is not added to the phosphorus-nitrogen expandable halogen-free flame retardant.

[0075] Comparative Example

[0076] Comparative Example 1-4: A high-rigidity flame-retardant polypropylene material, which is different from Example 1 in that the amounts of raw materials used are as shown in Table 2.

[0077] Table 2 Raw material dosage of low shrinkage flame retardant polypropylene material in comparative examples 1-4

[0078] Raw material / kg Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Homopolymer Polypropylene 20 30 0 50 Copolymer polypropylene 20 30 50 0 Long glass fiber 25 5 15 15 Halogen-free flame retardant 29 29 29 29 Toughening agent 5 5 5 5 Antioxidants 0.5 0.5 0.5 0.5 Lubricants 0.5 0.5 0.5 0.5

[0079] Comparative Example 5: A high-rigidity flame-retardant polypropylene material, which differs from Example 1 in that the halogen-free flame retardant is aluminum hydroxide.

[0080] Comparative Example 6: A high-rigidity flame-retardant polypropylene material, which differs from Example 1 in that package No. 1 and package No. 2 made of long glass fibers and halogen-free flame retardants are mixed and then directly added into the twin-screw extruder through the main feeding port.

[0081] Comparative Example 7: A flame-retardant, light-shielding, high-rigidity polypropylene composite material, comprising 29kg homopolypropylene, 10kg copolymer polypropylene, 5kg calcium sulfate whisker, 15kg long glass fiber, 5kg compatibilizer, 15kg titanium dioxide, 20kg flame retardant, 0.2kg antioxidant, 0.5kg lubricant, the crystallinity of the homopolypropylene is above 60%, and the melt flow rate is not less than 20g / 10min; the melt flow rate of the copolymer polypropylene is not less than 30g / 10min. The calcium sulfate whisker has an average diameter of 6-8um and an average length of 150-200um, and has been treated with a silane coupling agent in advance. The glass fiber is an alkali-free chopped glass fiber from Taishan Glass Fiber Company, with an average diameter of 11um, and has been treated with a silane coupling agent in advance. The compatibilizer is maleic anhydride grafted polypropylene with a grafting rate of 0.8%. The titanium dioxide is rutile and has been pre-treated with a silane coupling agent. The flame retardant is a compound of decabromodiphenylethane and antimony trioxide. The antioxidant is a phosphite antioxidant. The lubricant is vinyl bisstearamide.

[0082] The preparation method of the flame-retardant, light-shielding, high-rigidity polypropylene composite material comprises: weighing materials except calcium sulfate whiskers and glass fibers according to corresponding components and weight ratios, mixing in a high-speed mixer for 15 minutes, mixing the above raw materials evenly, and extruding the mixed blend through a twin-screw extruder for granulation; wherein the calcium sulfate whiskers are fed from the 6th zone side according to the corresponding weight ratio, and the glass fibers are fed from the 8th zone side according to the corresponding weight ratio. The temperatures of each zone of the extruder from the feeding section to the die head are 160°C, 170°C, 180°C, 190°C, 200°C, 200°C, 200°C, 190°C, and 185°C, respectively, the aspect ratio of the extrusion screw is 44, and the speed of the extrusion screw is 380 rpm.

[0083] Performance testing

[0084] The polypropylene material was prepared according to the method in the examples and comparative examples, and the performance was tested according to the following standards. The test results are recorded in Table 3.

[0085] 1. Tensile strength: Tested in accordance with ISO527-1-2012 "Determination of tensile properties of plastics";

[0086] 2. Flexural modulus: Tested in accordance with ISO178-2010 "Determination of flexural properties of plastics";

[0087] 3. Flame retardant grade: tested according to the flammability UL94 grade;

[0088] 4. Shrinkage after 48 hours: Tested in accordance with ISO294-4-2003 "Injection molding of plastics and thermoplastic material specimens Part 4: Determination of molding shrinkage";

[0089] 5. Gloss: Test according to ASTM D523-2018 "Standard Test Method for Specular Gloss".

[0090] Table 3 Performance test of low shrinkage flame retardant polypropylene material

[0091]

[0092]

[0093] It can be seen from the data in Table 3 that the polypropylene material prepared in Examples 1-4 has the advantages of high mechanical strength and good flame retardancy, and the bending modulus can reach 3002MPa, which can well inhibit the influence of post-shrinkage on the dimensional stability of the material and meet various use requirements. With the increase of the content of long glass fibers, the mechanical rigidity (strength and modulus) of the polypropylene material continues to increase, and the shrinkage rate continues to decrease.

[0094] In Example 5 and Example 6, the melt index of homopolypropylene is reduced and increased respectively, and in Example 7 and Example 8, the melt index of copolymer polypropylene is increased and decreased respectively. Table 3 shows that the tensile strength and flexural modulus of the polypropylene materials prepared in Examples 5-8 are reduced, and the mechanical strength is weakened.

[0095] Lubricants containing calcium stearate and silicone masterbatch were used in Examples 9 and 10, and the silicone masterbatch was prepared by Preparation Example 1 and Preparation Example 2, respectively. The data in Table 3 showed that the tensile strength and flexural modulus of the polypropylene materials prepared in Examples 9 and 10 were increased, the glossiness was significantly improved, and the shrinkage was slightly decreased.

[0096] Example 11 and Example 12 respectively use the silicone masterbatch prepared in Preparation Example 3 and Preparation Example 4. Compared with Example 9 and Example 10, the tensile strength and bending modulus of the polypropylene materials prepared in Example 11 and Example 12 are reduced, and the glossiness is reduced.

[0097] In Example 13, commercially available silicone masterbatch was used. Compared with Example 1, the mechanical strength and glossiness of the polypropylene material were improved, but compared with Examples 9 and 10, the mechanical strength and glossiness of the polypropylene material were reduced.

[0098] Compared with Example 1, in Example 14 and Example 15, no pyrophosphate piperazine carbonizing agent and polytetrafluoroethylene were added when preparing the phosphorus-nitrogen intumescent halogen-free flame retardant, and the flame retardant properties of the two were significantly reduced.

[0099] When the content of long-fiber glass fibers in Comparative Example 1 is increased to 25%, the flame retardancy of the material decreases to V1 compared with Example 1, indicating that too much long-fiber glass fibers affect the carbon-forming flame retardant effect of the halogen-free flame retardant.

[0100] In Comparative Example 2, the content of long-fiber glass fibers was reduced. Compared with Example 1, the flame retardant effect of the polypropylene material was weakened and the mechanical strength was reduced.

[0101] In Comparative Examples 3 and 4, homopolymer polypropylene and copolymer polypropylene were not added, respectively. Compared with Example 1, the tensile strength and bending strength of the polypropylene material decreased.

[0102] Compared with Example 1, in Comparative Example 5, aluminum hydroxide is used as a flame retardant, and the flame retardancy of the polypropylene material prepared therefrom decreases. In Comparative Example 6, long-fiber glass fiber and halogen-free flame retardant are blended with other raw materials and added through the main feed port, and the shrinkage rate of the polypropylene material increases.

[0103] Comparative Example 7 uses a polypropylene material prepared using prior art. Compared with Example 1, although it has stronger tensile strength and bending modulus, its shrinkage rate is large and its flame retardant performance is inferior to that of Example 1.

[0104] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-rigidity flame-retardant polypropylene plastic, characterized in that: The invention comprises the following raw materials in weight percentage: 20-30% homopolypropylene, 20-30% copolymer polypropylene, 15-20% long glass fiber, 20-30% halogen-free flame retardant, 2-8% toughening agent, 0.5-1.5% antioxidant and 0.5-1.5% lubricant. The halogen-free flame retardant is a phosphorus-nitrogen expansion type halogen-free flame retardant.

2. The high rigidity flame retardant polypropylene plastic according to claim 1, characterized in that: The polypropylene plastic comprises the following raw materials in percentage by weight: 25% homopolymer polypropylene, 25% copolymer polypropylene, 15% long-fiber wollastonite, 29% halogen-free flame retardant, 5% toughening agent, 0.5% antioxidant, and 0.5% lubricant.

3. The high rigidity flame retardant polypropylene plastic according to claim 1, characterized in that: The phosphorus-nitrogen intumescent halogen-free flame retardant comprises high-polymerization II type melamine polyphosphate salt, piperazine pyrophosphate and polytetrafluoroethylene in a mass ratio of 5:1-1.2:0.05-0.

1.

4. The high rigidity flame retardant polypropylene plastic according to claim 1, characterized in that: The lubricant comprises a stearic acid lubricant and a silicone masterbatch in a mass ratio of 1:0.8-1.

2.

5. The high rigidity flame retardant polypropylene plastic according to claim 4, characterized in that: The silicone masterbatch is prepared by the following method: dispersing silicone powder in anhydrous ethanol to prepare a dispersion with a concentration of 8-10wt%; adding attapulgite into deionized water to prepare a suspension with a concentration of 3-5wt%; adding silica sol into deionized water to prepare a silica sol solution with a concentration of 3-5wt%; The dispersion, suspension and silica sol solution are mixed and spray-dried to obtain silicone masterbatch, wherein the mass ratio of silicone powder, silica sol and attapulgite is 2-2.5:2.5-3:

5.

6. The high rigidity flame retardant polypropylene plastic according to claim 1, characterized in that: At 230° C. and 2.16 kg, the melting index of the homopolypropylene is 10-20 g / 10 min, and the melting index of the copolymer polypropylene is 20-30 g / 10 min.

7. The high rigidity flame retardant polypropylene plastic according to claim 1, characterized in that: The toughening agent is ethylene-octene copolymer, and the melt index under the conditions of 190° C. and 2.16 kg is 20 g / 10 min.

8. The high rigidity flame retardant polypropylene plastic according to claim 1, characterized in that: The antioxidant is selected from one or more of phosphite antioxidants, thioester antioxidants and hindered antioxidants.

9. The method for preparing the high rigidity flame retardant polypropylene plastic according to any one of claims 1 to 8, characterized in that: The following steps are involved: Preparation of halogen-free flame retardant: high polymerization degree II type polyphosphate melamine salt is stirred at high speed at 30-40°C for 10-12 minutes, piperazine pyrophosphate carbonizing agent is added, the temperature is raised to 60-70°C, stirred at high speed for 60-70 minutes, cooled to 20-30°C, polytetrafluoroethylene is added while stirring, stirred at low speed for 5-8 minutes, cooled for 20-25 minutes, and the halogen-free flame retardant is obtained; Raw material selection: according to the mass percentage, weigh 20-30% homopolypropylene, 20-30% copolymer polypropylene, 15-20% long glass fiber, 20-30% halogen-free flame retardant, 2-8% toughening agent, 0.5-1.5% antioxidant and 0.5-1.5% lubricant respectively; Mixing and stirring: adding the halogen-free flame retardant to the long glass fiber, stirring at 20-30°C for 30-40 minutes, to obtain a No. 1 material package; mixing the homopolymer polypropylene, copolymer polypropylene, toughening agent, antioxidant and lubricant, stirring at 20-30°C for 30-40 minutes, to obtain a No. 2 material package; Blending modification: Add No. 2 material package to the main feeding port, add No. 1 material package through the side feeding port, the extrusion temperature is 180-220℃, extrude the strip material, and cool; Air-cooling pressing: Arrange the strip materials in sequence at a spacing of 2-5 cm, cool them with cold air at 15-16°C for 25-35 minutes, press them at a pressure of 1-2 MPa for 5-10 seconds, and package them to obtain high-rigidity flame-retardant polypropylene materials.

10. The method for preparing high-rigidity flame-retardant polypropylene plastic according to claim 9, characterized in that: During extrusion, the screw speed is 320-350r / min and the extrusion power is 260-280W.

Citation Information

Patent Citations

  • Low-shrinkage flame-retardant polypropylene plastic and preparation method thereof

    CN117285775A